2006
DOI: 10.1002/ejoc.200600044
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Reactions of New Optically Active Terpene Dialkyl Diselenides

Abstract: The reaction of sodium diselenide with optically active alkyl tosylates or chlorides is found to be a useful method for the synthesis of optically active dialkyl diselenides. Optically active monoterpene diselenides derived from menthane, carane, pinane, and bornane systems have been obtained. The influence of the terpene fragment of the obtained diselenides on the diastereomeric excess of the methoxyselenylation products has been investigated. The best result for methoxyselenylation was observed for (–)‐diiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…Substrate 14 was converted to corresponding chloride 15 and tosylate 16 by standard procedures described in previous papers. 20 In the next step, (-)-myrtenol 28 was converted into myrtenyl trityl ether 29. Hydroboration oxidation to alcohol 30, followed by mesylation and nucleophilic substitution with sodium diselenide yielded diselenide 32.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substrate 14 was converted to corresponding chloride 15 and tosylate 16 by standard procedures described in previous papers. 20 In the next step, (-)-myrtenol 28 was converted into myrtenyl trityl ether 29. Hydroboration oxidation to alcohol 30, followed by mesylation and nucleophilic substitution with sodium diselenide yielded diselenide 32.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our research group has synthesised several examples of terpenyl diselenides, bearing an additional heteroatom, and transformed them into corresponding electrophiles and used these as reagents in the asymmetric selenenylation of olefins and selenocyclization of unsaturated alcohols and acids. [19][20][21][22][23][24][25][26] Application of dipinocamphyl diselenides 8 and 9 substituted with phenylselenyl and pentafluorophenoxy groups resulted in good diastereomeric ratios with moderate yields. For diselenide 10, bearing a hydroxyl group, the diastereomeric excess was minimal.…”
Section: Introductionmentioning
confidence: 99%
“…Having access to optically active (þ)-dineomenthyl [59] and (À)-bis(cis-myrtanyl) diselenides [60] we also decided to take advantage of this straightforward reaction. We found that 1,1 0 -dilithioferrocene smoothly reacts with either of above mentioned optically active terpene dialkyl diselenides in hexane at room temperature to afford in each case a mixtures of mono-terpenylseleno (2a or 2b) and 1,1 0 -bis(terpenylseleno) ferrocenes (1a or 1b) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…1,1 0 -Dilithioferrocene was prepared according to the literature procedure [58]. Optically active terpene dialkyl diselenides have been obtained according to known procedures [59,60].…”
Section: General Remarksmentioning
confidence: 99%
“…Considering their usage in organic synthesis diselenides possess several advantages -they are stable and can be easily converted to electrophilic, nucleophilic and radical reagents. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The biological potential of diaryl diselenides is mainly associated with their GPx-like activity. Glutathione peroxidase (GPx) is a selenoenzyme that, based on the presence of catalytically active aminoacid selenocysteine (Sec, U), eliminates reactive oxygen and nitrogen species enabling to maintain the redox homeostasis inside the cell.…”
Section: Introductionmentioning
confidence: 99%